Seasonal Variation in TP53 R249S-Mutated Serum DNA with Aflatoxin Exposure and Hepatitis B Virus Infection - Villar, Stéphanie (National Institute of Environmental Health Sciences, 2011)
Background: Chronic hepatitis B virus (HBV) infection and dietary aflatoxin B(1) (AFB(1)) exposure are etiological factors for hepatocellular carcinoma (HCC) in countries with hot, humid climates. HCC often harbors a TP53 (tumor protein p53) mutation at codon 249 (R249S). In chronic carriers, 1762(T)/1764(A) mutations in the HBV X gene are associated with increased HCC risk. Both mutations have been detected in circulating cell-free DNA (CFDNA) from asymptomatic HBV carriers. Objective: We evaluated seasonal variation in R249S and HBV in relation to AFB(1) exposure. Methods: R249S was quantitated by mass spectrometry in CFDNA in a cross-sectional survey of 473 asymptomatic subjects (237 HBV carriers and 236 noncarriers) recruited in three villages in the Gambia over a 10-month period. 1762(T)/1764(A) HBV mutations were detected by quantitative polymerase chain reaction. In addition, the HBV S gene was sequenced in 99 subjects positive for HBV surface antigen (HBsAg). Results: We observed a seasonal variation of serum R249S levels. Positivity for R249S and average concentration were significantly higher in HBsAg-positive subjects surveyed during April–July (61%; 5,690 ± 11,300 R249S copies/mL serum) than in those surveyed October–March [32% and 480 ± 1,030 copies/mL serum (odds ratio = 3.59; 95% confidence interval: 2.05, 6.30; p < 0.001)]. Positivity for HBV e antigen (HBeAg) (a marker of HBV replication) and viral DNA load also varied seasonally, with 15–30% of subjects surveyed between April and June HBeAg positive, compared with < 10% surveyed during other months. We detected 1762(T)/1764(A) mutations in 8% of carriers, half of whom were positive for R249S. We found HBV genotype E in 95 of 99 HBsAg-positive subjects. Conclusion: R249S is detectable in CFDNA of asymptomatic subjects. Evidence of temporal and quantitative variations suggests an interaction among AFB(1) exposure, HBV positivity, and replication on TP53 mutation formation or persistence.